PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI (Studi Pada: Pegawai Badan Narkotika Nasional Provinsi Bengkulu) - Utami, Haryati (JURNAL EKOMBIS REVIEW, 2016)
The purpose of this study was to determine the effect of organizational culture, leadership style and organizational commitment to the performance of the employees of National Narcotics Board in Bengkulu Province either simultaneously or partially. This research is used multiple linear regression with respondents 59 employees of the employees of National Narcotics Board in Bengkulu Province. Data collection methods used were questionnaires and interviews. Methods of quantitative data analysis is done by finding the average value (mean) of the scaling (scoring) of data and processing research data using SPSS 17 software. These results from the study hypothesis test indicate that the organizational culture, leadership style and organizational commitment to the performance of the employees of National Narcotics Board in Bengkulu province has an influence either simultaneously or partially.  Keywords: Organizational Culture, Leadership Style And Organizational Commitment And Employee Performance.